Some reflections on the correspondence between Jan Cep and Henri Pourrat - Zatloukal, Jan (Romanica Olomucensia, 2014)
Jan Cep, translator of Gaspard from the Mountains, belonged among the important non-French correspondents of Henri Pourrat. Their mutual correspondence (1932-1958), which reflects notable moments of European history of the twentieth century, is an important source not only for the literary historian. Based on this correspondence, the paper analyzes three aspects of literary reflection: how the two letter writers comment on the literary production of the time (letter as a document); how the writer critically reflects his own work (letter as a critical space); what is the relation of the correspondence and the literary creation (letter as a piece of writing).
Keywords: Jan Cep; Henri Pourrat; correspondence; literary production; work in progres.